2022
DOI: 10.1136/bmjopen-2021-060169
|View full text |Cite
|
Sign up to set email alerts
|

Five-year follow-up of patients with knee osteoarthritis not eligible for total knee replacement: results from a randomised trial

Abstract: ObjectivesThe main objective was to investigate 5-year outcomes in patients with knee osteoarthritis, randomised to one of two non-surgical treatments.SettingTwo outpatient clinics.ParticipantsAt baseline, 100 patients with radiographic and symptomatic knee osteoarthritis not found eligible for knee replacement (KR) were included. Main exclusion criteria were average score above 75 of the Knee injury and Osteoarthritis Outcome Score (KOOS) subscales pain, symptoms, function of daily living and quality of life;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
(97 reference statements)
0
1
1
Order By: Relevance
“…The 5-year TKR incidence rate that was found in the study was 18.4%, which is significantly lower than the natural decay rate reported among patients presenting with similar symptoms [26][27][28]. As a conservative comparison, Larsen, et al demonstrated a 30% to 34% TKR incidence over five years among newly diagnosed patients with knee OA who were not initially eligible for surgery [25].…”
Section: Discussioncontrasting
confidence: 51%
“…The 5-year TKR incidence rate that was found in the study was 18.4%, which is significantly lower than the natural decay rate reported among patients presenting with similar symptoms [26][27][28]. As a conservative comparison, Larsen, et al demonstrated a 30% to 34% TKR incidence over five years among newly diagnosed patients with knee OA who were not initially eligible for surgery [25].…”
Section: Discussioncontrasting
confidence: 51%
“…This enhances treatment efficacy and aids in refining patient selection criteria, optimising resource utilisation, and minimising potential risks. Identifying biomarkers is critical for tailoring regenerative therapies to individual patient profiles, ultimately improving overall treatment outcomes [ 47 ].…”
Section: Reviewmentioning
confidence: 99%